HUBUNGAN USIA DAN DURASI LAMA DUDUK DENGAN KELUHAN NYERI PUNGGUNG BAWAH PADA PEMBATIK DIKAMPUNG BATIK GIRILOYO - Lailatuz Zaidah; Novia Triwulandari (LPPM Universitas Abdurrab, 2019)
Background: Batik makers work with non-ergonomic work position and work attitude for more than 8 hours, causing musculoskeletal complaints on the hands, neck and back. From the results of interviews and questionnaires, 12 of 20 batik makers complained about pain in their lower back. Objective: The study aims to determine the correlation between age and duration of sitting and low back pain complaints in batik makers in Kampung Batik of Giriloyo. Method: The study employed analytic observation method with a case control approach and purposive sampling technique. The data analysis used Chi-Square statistical test. The sample in this study was batik makers in Kampung Batik of Giriloyo, totaling 54 batik makers of the control group and 54 batik makers in the case group. Result: There was a correlation between age and low back pain complaints (p = 0.031 <0.05 OR = 9.217). in addition, there was a correlation between duration of sitting and low back pain complaints (p = 0.027 <0.05 OR = 2.125). Conclusion: Age â‰¥ 30 years is 9 times more at risk than <30 years old. Duration of sitting â‰¥ 4 hours is 2 times more at risk than the duration of sitting <4 hours. Suggestion: Further researchers are expected to conduct research on other factors that can affect low back pain in batik makers.